Rentenreform – mit welchem Fokus? - Franz Ruland; Friedrich Breyer; Winfried Schmähl; Tim Köhler-Rama; Volker Meinhardt (Wirtschaftsdienst, 2016)
Der Altenquotient steigt deutlich an, das Rentenniveau sinkt. Dies fordert politisches Handeln heraus. Noch in diesem Herbst will Sozialministerin Andrea Nahles Eckpunkte einer Reform der Alterssicherung vorstellen. Stellschrauben gibt es genug: Die betriebliche Altersvorsorge kann besser gesichert, die private Rentenversicherung ausgebaut, die Beitragsbasis in der gesetzlichen Rentenversicherung erweitert, das Renteneintrittsalter angehoben und staatliche Zuschüsse können erhöht werden. Die Autoren sind sich durchaus nicht darüber einig, wo der dringendste Handlungsbedarf besteht und ob nicht gar das ganze System zurückgedreht werden sollte. – – The demographic imbalance is aggravating, and by 2060 the old-age dependency ratio will double to approximately 70%. This development has consequences for the state pension system: growing contribution rates to social security coupled with lower pension levels, but at the same time a higher retirement age. The German pension scheme is mandatory for all wage and salary earners, but since 2001, no reasonable indicator for measuring the pension level exists any more. As a consequence of this, old-age pension has lost its traditional function as a replacement for earnings. The recent pension reforms have dropped the pension level sharply. Further reductions have been announced with the consequence of increasing old age poverty. Against this background it is proposed to raise the pension level so that the pensioners can maintain their standard of living. But any pension reform involves issues of distribution between and often also within generations, which cannot be addressed without explicit equity criteria. Some authors consider the past reforms as a mistake, others suggest adjustments.
Keywords: 330